Estimating the Income and Substitution Effects on the Demand for Poultry Meat - Mohamed, Zainal Adidin; A. Ghaffar, Roslan (1989)
This study attempts to analyze the factors underlying the demand and consumption trends of POUltry meat in Malaysian. Specifically, it explores the poultry, meat consumption due to changes in prices and income and the interaction in demand between floury meat and the components of the rest of the meat market. To obtain the parameters of the demand model for poultry meat, two estimation techniques were used in estimating the demand model, namely single and instrumental variables approach, while Slutsky equations were utilized to estimate the income and substitution effects of poultry meat with the other components of the meat ma diet. The results indicate that poultry meat is a normal good while both beef and pork are substitutes to poultry, meat. However, mixed results were obtained for poultry meat and fish. Based on the magnitude of the substitution effect and cross p17ce elasticity, it is concluded that the demand for fish is independent of the other components of the meat market.